METTL3 Accelerates Breast Cancer Progression via Regulating EZH2 m6A Modification. (29th March 2022) - Hu, Shaojun; Song, Yang; Zhou, Yu; Jiao, Yu; Li, Guopeng
Abstract : We aimed to investigate the bio-functions of METTL3 in promoting breast cancer (BCa) progression via regulating N6-methyladenosine (m 6 A) modification of EZH2 mRNA. METTL3 levels in 48 cases of BCa and matched paracancerous tissues were detected. In the meantime, METTL3 in BCa patients with different staging or lymphatic metastasis states were examined. Prognosis of the BCa patients was analyzed using Kaplan–Meier estimator. Protein levels of EMT-associated genes and invasive and migratory abilities were evaluated. The binding relationship between EZH2 and METTL3 was analyzed via RIP. Besides, m 6 A modification of EZH2 mRNA was explored. E-Cadherin level in MCF-7 cells with EZH2 knockdown was tested. Subsequently, ChIP was done to verify the interaction between E-cadherin and EZH2. Regulatory effects of METTL3/E-cadherin axis on EMT and metastasis of BCa were finally determined. METTL3 was upregulated in BCa tissues compared to paracancerous ones. METTL3 was especially higher in T3-T4 BCa or those with lymphatic metastasis. BCa patients expressing high level of METTL3 experienced worse survival. METTL3 was identically upregulated in BCa cell lines. Knockdown of METTL3 in MCF-7 cells attenuated EMT and metastatic abilities. Protein level of EZH2 was downregulated after knockdown of METTL3 in MCF-7 cells, while its mRNA level was not influenced by METTL3. Furthermore, METTL3 was confirmed to interact with EZH2, and m 6 A modification existed in EZH2 mRNA. Knockdown of EZH2 greatly upregulated mRNA level of E-cadherin, and later, ChIP assay confirmed the interaction between EZH2 and E-cadherin. E-Cadherin could abolish the effects of METTL3 on BCa metastasis and epithelial-mesenchymal transition. METTL3 is upregulated in BCa. It could regulate the protein level of EZH2 through m 6 A modification to promote EMT and metastasis in BCa cells, thereafter aggravating the progression of BCa.